2020
DOI: 10.3390/s20010305
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Wood Behaviour: The Use of Strain Gauges for Preventive Conservation Applications

Abstract: Within the heritage field, the application of strain gauges on wood surfaces is a little-explored but inexpensive and effective method to analyse the environmental appropriateness of rooms for the wooden heritage collections they contain. This contribution proposes a wood sensor connected to a data logger to identify short moments with an elevated risk of harm. Two experiments were performed to obtain insights pertaining to the applicability of wood sensors to evaluate preservation conditions. (1) The represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Results from our review showed limited data on the effectiveness and/or safety of IOs in patients with Exon 20ins, however, ongoing research will further assess the impact of PD-1/PD-L1 blockade in these patients, given recent findings that patients with EGFR Exon 20ins had increased PD-L1 expression and improved outcomes compared to those with HER2 Exon 20ins [61]. In addition, several emerging compounds, such as DS-2087b [62] and BLU-945 [63], have demonstrated antitumour activity in preclinical studies. It should be noted that most studies identified in this SLR included a small number of patients with Exon 20ins, and there was considerable heterogeneity in the clinical and demographic characteristics of the enrolled patients.…”
Section: Discussionmentioning
confidence: 93%
“…Results from our review showed limited data on the effectiveness and/or safety of IOs in patients with Exon 20ins, however, ongoing research will further assess the impact of PD-1/PD-L1 blockade in these patients, given recent findings that patients with EGFR Exon 20ins had increased PD-L1 expression and improved outcomes compared to those with HER2 Exon 20ins [61]. In addition, several emerging compounds, such as DS-2087b [62] and BLU-945 [63], have demonstrated antitumour activity in preclinical studies. It should be noted that most studies identified in this SLR included a small number of patients with Exon 20ins, and there was considerable heterogeneity in the clinical and demographic characteristics of the enrolled patients.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, it is challenging to measure precious wood materials due to the use of a strong adhesive, which can destroy the wood after removal. For example, the heritage community generally does not allow the application of strain gauges on wooden arts (Anaf et al 2020). Moreover, difficulties arise when strain gauges are used in an environment where the electromagnetic wave interference is extensive (Liu et al 2015;Barr et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the mentioned parameters, various sensors such as temperature and humidity sensors [68], accelerometers [69], vision-based systems [70], inclinometers [71], strain gauges [72], robotically deployed sensors [73], etc, are widely used in long-term monitoring systems. These systems are meticulously designed to capture real-time data on diverse structural parameters critical to the safety and reliability of glass elements.…”
Section: Data Acquisitionmentioning
confidence: 99%